Mycoplasma hominis Meningitis in a 24 Week Premature Neonate: Case Report and Short Literature Review - Watson, Louise (Pediatric Pharmacy Advocacy Group, 2008)
Over the last 20-year period there have been fewer than 10 reported cases of Mycoplasma hominis central nervous system infection in either premature or full term infants. The optimum management of M hominis infection in premature infants is still unclear. We report the case of a premature infant with persistent central nervous system infection caused by M hominis treated successfully with intravenous chloramphenicol. Previous reports of M hominis central nervous infection and its management are reviewed.